The Application of a Monoclonal Antibody to Factor VIII Related Antigen (VIIIRAg) in Immunoradiometric Assays for Factor VIII - Thomas, J E; Peake, I R; Giddings, J C; Welch, A N; Bloom, A L (Thrombosis and Haemostasis, 1985)
A two site solid phase immunoradiometric assay (IRMA) for VIIIRAg has been developed using a monoclonal antibody as both the solid phase ligand and the radiolabelled antibody. A range of normal plasmas and von Willebrand’s disease (vWd) plasmas has been assayed for VIIIRAg by this method and compared with VIIIRAg values measured by an IRMA using polyclonal antibodies and by immunoelectrophoresis and with ristocetin cofactor activity (VIIIRiCoF). It was found that the monoclonal IRMA correlated well with the polyclonal IRMA and the immunoelectrophoretic assay, but the correlation with the VIIIRiCoF assay was relatively poor, in spite of the strong inhibitory effect of the antibody on VIIIRiCoF activity.
Keywords: Factor VIII; Monoclonal antibodies; Immunoradiometric assays